Managing Flood Risk in Guyana : The Conservancy Adaptation Project, 2008-2013 - Bovolo, Isabella (World Bank, Washington, DC, 2014)
The East Demerara Water Conservancy (EDWC) and east coast drainage and irrigation systems provide water storage and flood control mechanisms for Guyana's most populous region, including the capital city of Georgetown. In 2005, extreme rainfall caused devastang flooding along these coastal lowlands, with many areas remaining inundated for up to three weeks. The flood highlighted the vulnerability of the EDWC dam to overtopping and potential breaching. The Conservancy Adaptation Project (CAP) was conceived in the wake of the 2005 flood to help the Government of Guyana adapt to the threats posed by future climate change. The aim was to reduce the likelihood of catastrophic flooding along Guyana's low-lying coastal areas, also threatened by sea level rise. The project identified key investments totaling over US$ 123 million. These are being used by the Government to update the national master-plan strategy for drainage and irrigation and to plan future investment programs for reducing flood risk.